If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 13 = -64 + -8 Reorder the terms: 13 + 3x = -64 + -8 Combine like terms: -64 + -8 = -72 13 + 3x = -72 Solving 13 + 3x = -72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 3x = -72 + -13 Combine like terms: 13 + -13 = 0 0 + 3x = -72 + -13 3x = -72 + -13 Combine like terms: -72 + -13 = -85 3x = -85 Divide each side by '3'. x = -28.33333333 Simplifying x = -28.33333333
| -6x^2+4x^3+2-2x=0 | | -r^5+3r^4-12r= | | 5(2x-2)-2x=22 | | 112-(5x+6)=5(x+8)+x | | 1-3p=11 | | 6m-5=25 | | 3(2x+1)+3x=39 | | 3+3=m | | 16v^3+36v^2-112v=0 | | 12-10x=48-24x | | 5+2*x=7-4*x | | 5(x-1)-4=11 | | p^2-q^2-36= | | y=1x+8 | | 4(x+12)=14-2(3-4x) | | 3(x+2)-4=20 | | p-2=59 | | 5x-12=-x | | 61=7x+12 | | (x*6)+(2x*6)=18000000 | | 5x-12=3*(x+2) | | -4x+10=2(3x-20) | | 11+8x=91 | | 6n-4=-2n+44 | | 4-2x-38y+19xy= | | 2(3y-4)=8y-18 | | 3*2=m | | 6(x-5)+2=14 | | 6x+5=-1(-4x+9) | | g(x)=2x^2+8x+3 | | -82.5+(-15t)=2.8-3t | | 20x^2+21-5= |